Oral health-related quality of life in children: Part III. Is there agreement between parents in rating their children’s oral health-related quality of life? A systematic review - TS Barbosa (Journal compilation 2008 Blackwell Munksgaard, 2008)
One issue that receives a great deal of attention is the comparison between measurement of children’s oral health-related quality of life (OHRQoL) reports with those of their parents.